Washington's Iron Butterfly Bess Clements Abell, an oral history - Ritchie, Donald A., 1945-; Birdwhistell, Terry L.; Smith, Richard Norton, 1953- (University Press of Kentucky, 2022)
"Had Elizabeth "Bess" Clements Abell (1933-2020) been a boy, she would likely have become a politician like her father, Earle C. Clements. Effectively barred from office because of her gender, she forged her own path by helping family friends Lyndon and Lady Bird Johnson. Abell's Secret Service code name, "Iron Butterfly," exemplified her graceful but firm management of social life in the Johnson White House. After Johnson's administration ended, she maintained her importance in Washington, DC, serving as chief of staff to Joan Mondale and cofounding a public relations company. Donald A. Ritchie and Terry L. Birdwhistell draw on Abell's own words and those of others known to her to tell her remarkable story. Focusing on her years working for the Johnson campaign and her time in the White House, this engaging oral history provides a window into Abell's life as well as an insider's view of the nation's capital during the tumultuous 1960s"-- Provided by publisher.
Keywords: Abell, Bess Clements, -- 1933-2020 -- Interviews.; United States. -- White House Office -- Officials and employees.; Johnson, Lady Bird, -- 1912-2007 -- Friends and associates.; Johnson, Lyndon B. -- (Lyndon Baines), -- 1908-1973 -- Friends and associates.; Johnson, Lyndon B. -- (Lyndon Baines), -- 1908-1973; Johnson, Lady Bird, -- 1912-2007; United States. -- White House Office; Presidents -- United States -- Staff -- Biography.; Social secretaries -- Washington (D.C.) -- Biography.; Washington (D.C.) -- Social life and customs -- 1951-; Kentucky -- Biography.; Secrétaires privés -- Washington (D.C.) -- Biographies.; Washington (D.C.) -- Mœurs et coutumes -- 1951-; Kentucky -- Biographies.; Political.; BIOGRAPHY & AUTOBIOGRAPHY.; Women.; HISTORY.; Social secretaries; Presidents -- Staff; Manners and customs; Friendship; Employees; Washington (D.C.); United States; Kentucky; Since 1951; Electronic books.; Interviews; Biographies